Fluorescence anisotropy (polarization): from drug screening to precision medicine - Zhang, Hairong (Expert Opin Drug Discov, 2015)
INTRODUCTION: Fluorescence anisotropy (FA) is one of the major established methods accepted by industry and regulatory agencies for understanding the mechanisms of drug action and selecting drug candidates utilizing a high-throughput format. AREAS COVERED: This review covers the basics of FA and complementary methods, such as fluorescence lifetime anisotropy and their roles in the drug discovery process. The authors highlight the factors affecting FA readouts, fluorophore selection, and instrumentation. Furthermore, the authors describe the recent development of a successful, commercially valuable FA assay for Long QT syndrome drug toxicity to illustrate the role that FA can play in the early stages of drug discovery. EXPERT OPINION: Despite the success in drug discovery, the FA-based technique experiences competitive pressure from other homogeneous assays. That being said, FA is an established yet rapidly developing technique, recognized by academic institutions, the pharmaceutical industry, and regulatory agencies across the globe. The technical problems encountered in working with small molecules in homogeneous assays are largely solved, and new challenges come from more complex biological molecules and nanoparticles. With that, FA will remain one of the major work-horse techniques leading to precision (personalized) medicine.